E-cigarette or vaping product use-associated lung injury (EVALI) epidemy of 2019 and how to prevent it from happening again – a review. - Alabrudziński, Konstanty; Wilewska, Anna; Pomirski, Bartosz; Biernikiewicz, Julia; Biernikiewicz, Milena; Pomirska, Agata; Borowiec, Agnieszka; Kwaśniewska, Paulina; Borowiec, Kinga; Dach, Aleksandra (Journal of Education, Health and Sport, 2024)
The EVALI (E-cigarette or Vaping product use-Associated Lung Injury) epidemic of 2019 was a major public health challenge, attracting the attention of both the scientific community and the public. In a short period of time, thousands of cases of acute lung injuries and deaths were reported among e-cigarette users, previously unrelated to the risk, shedding new light on the safety of these devices and exposing gaps in the regulations regarding their use. This paper aims to review the literature on the EVALI epidemic, with particular emphasis on epidemiology, identification of the etiological agent, clinical presentation and treatment. Based on the collected data, the authors also analysed the possibilities of preventing similar events in the future, emphasizing regulations, health education of patients and increasing physicians’ awareness of EVALI.